Measuring the level of muzakki satisfaction on Zakat institution performance - Lahuri, Setiawan bin; Ahmad, Rusyda Afifah; Zahroturrosyidah, A’isa; Maulana, Hartomi; Affandi, Muchammad Taufiq (Jurnal Ekonomi & Keuangan Islam, 2025)
Purpose – This study aimed to measure muzakki satisfaction through institutional image zakat institutions’ performance and expectation disconfirmation theory.Methodology – This study uses Structural Equation Modeling Partial Least Squares (SEM-PLS) supported by SmartPLS 3.0, with a quantitative approach to measure muzakki satisfaction. Data were collected using a questionnaire, totaling 395 respondents from all branches of the Baitul Mal TAMZIS office.Findings – This study shows that institutional image, zakat institution performance, and desire disconfirmation have a significant positive effect on muzakki satisfaction, while expectation disconfirmation and perceived performance do not have a significant effect. This was supported by systematic programs and strategies, transparent reporting, and the use of electronic money to facilitate muzakki. Baitul Mal TAMZIS, with 42 branches spread across Wonosobo, Yogyakarta, Central Java, and West Java, continues to increase the collection and distribution of Zakat, Infaq, Sadaqah, and Waqf (ZISWAF) funds, with 70% of the muzakki becoming regular donors.Implications – The results of this study can be used by policymakers of Islamic Social Institutions such as Zakat Institutions, by paying attention to the image of the institution and the performance of zakat institutions.Originality – This study uses the theory of expectation disconfirmation, which is usually applied to non-profit institutions, to measure muzakki satisfaction in zakat institutions. The application of this theory in the context of zakat has not been widely explored, thus providing a new contribution to the literature on zakat management.